The Association between Smoking Cigarettes and Anxiety among High School Students - Leman, Gabriel Kevin; Hardi, Nicholas; Johanna, Aila (Journal of Urban Health Research, 2024)
Introduction: Cigarette use and nicotine dependence in adolescents are increasing. Nicotine dependence can cause anxiety. This study aimed to investigate the relationship between smoking and anxiety in high school students. Methods: This was a cross-sectional study with a case-control design. 160 male students (80 with anxiety, 80 without anxiety) participated in the study. Active smokers were students who smoke, and non-smokers were students who did not smoke at the time of data acquisition. Anxiety was evaluated using the Hamilton Anxiety Rating Scale (HAM-A) instrument. Chi-square was applied to analyze the association between smoking habits and anxiety. Significance was set at p < 0.05. Results: The number of smokers and non-smokers were 75 (47%) and 85 (53%). Most students had mild-moderate anxiety (76/95%). Among students with anxiety, 48 (60%) were smokers, while in students without anxiety, only 27 (33.7%) were smokers. Anxiety was associated with smoking habits (OR 2.94, 95%CI 1.55 – 5.61, p=0.001). Conclusions: Smokers have a 2.9 possibility of experiencing anxiety compared to non-smokers in high school students.   Keywords: nicotine dependency - cigarette use - anxiety - high school students - negative outcome.